Anemia in diabetes mellitus: Pathogenetic aspects and the value of early erythropoietin therapy - Christina Antoniadou; Efstratios Gavriilidis; Konstantinos Ritis; Dimitrios Tsilingiris (Metabolism Open)
Anemia is a frequent, yet increasingly recognized, comorbidity in diabetes mellitus (DM), with prevalence often driven by multifactorial mechanisms. Hematinic deficiencies, common in this population, may arise from associated comorbidities or medications, such as metformin, as well as other drugs commonly employed for DM-related conditions. Among contributing factors, diabetic kidney disease (DKD) plays a pivotal role, with anemia developing more frequently and being more pronounced in earlier stages, than in CKD of other causes. This enhanced susceptibility stems primarily from the combined impact of impaired renal oxygen sensing and deficient erythropoietin (EPO) production linked to tubulointerstitial fibrosis. Additional mechanisms comprise glomerular dysfunction, shortened erythrocyte lifespan, uremia-induced bone marrow suppression, and increased bleeding risk. DM is also recognized as a chronic low-grade inflammatory condition, with its inflammatory burden driving iron maldistribution, suppression of erythropoiesis, and resistance to EPO. The diagnostic approach of anemia in DM mirrors that in the general population. Addressing modifiable causes such as hematinic deficiencies, and other chronic conditions, such as DKD and bone marrow disorders, is paramount. In total, the underlying pathophysiology of anemia in DM primarily reflects a state of absolute or relative EPO deficiency and/or diminished bone marrow responsiveness, effectively corresponding to 'anemia of chronic disease. Early initiation of EPO therapy, even in DM patients without overt DKD, may mitigate disease progression and improve outcomes. Future research should focus on diabetes-specific strategies integrating optimal EPO use, potentially implementing targeted management of renal and inflammatory contributors to anemia.